Intercultural competence in education export : a case study of Finnish teacher training programme for Chinese teachers - Cao, Jian (2020)
The issue that this study addresses is the lack of knowledge on the impacts of different cultures in Finland-to-China education export. To address this problem, the purpose of this case study is to investigate on the cultural differences in Finland-China teacher training programmes, and the impacts of these cultural differences on the training quality. To gather data, interviews with seven Chinese teachers from different Chinese institutions and one Finnish trainer, in the case of JAMK Teacher Training Programme for Chinese Teachers, were conducted from March to October in 2018. The interviews were transcribed and analysed from a theoretical perspective of intercultural competence. The results showed that in the Finland-to-China education export, Chinese trainees have observed the differences of cultures between Finland and China in the aspects of trust in the society, educational traditions and practical arrangements in daily routines. Furthermore, the study indicated a lack of a proper channel for information sharing and mutual learning on the cultures of Finland and China, which led to the difficulties for Chinese trainees to understand the Finnish experiences, society and culture during the training, thus diminishing the training quality. Nevertheless, the study also suggested if the Chinese trainees and Finnish trainers can be aware of the cultural differences in advance, and take actions to overcome the cultural obstacles, the training is a mind-opening opportunity. In this case, the Chinese trainees were inclined to implement the Finnish experiences in their future work. The findings of this study can be used by Finnish higher education institutions, private educational providers for improving their educational export practices to China. The study will also contribute to promoting the educational cooperation and exchanges between Finland and China.